Pengembangan Sistem Informasi Pemesanan Produk Pada PT. Temprina Media Grafika Menggunakan Zachman Framework - Hilwa Aminatus Sholihah; Yusi Tyroni Mursityo; Nanang Yudi Setiawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Temprina Media Grafika is part of Jawapos Group engaged in printing and packaging services. Printing services are provided using the latest graphic technology such as high-tech printing machines so as to support the quality and quality of the products produced. But now with a sophisticated printing machine, there are several problems related to the lack of integration of customer transaction data for each division in all branches of the company. This causes the work to be less flexible and take longer time to handle it for employees. Besides the problem, there is still insufficient information given regarding the production stage of ordered items to customers. Therefore, an information system is needed to support the product ordering process. In this study, the development of information systems uses the Zachman framework because it is a logical structure to clarify and organize companies that are significant to the system development so as to get a complete organization depiction. The output of this research is the product ordering system prototype which is the result of implementation of 4 perspectives used, namely the perspective of planners, owner/ analysts, designers, and builders. Then, testing the product ordering system prototype with blackbox testing using 38 test cases which produced 100% valid result and compatibility testing using sortsite software which produced 2 critical issues in 2 browsers. The last test is user acceptance test which results in an 84.3% value for customers and 84.6% value for employees. Based on the test results above, it can be concluded that they strongly agrees with the system.